A varnished cloth for photovoltaic module lamination technology - WANG XIAOWEI; XU TAO; JI XU; YANG FENG (2018)
The utility model discloses a varnished cloth for photovoltaic module lamination technology relates to solar cell technical field. A varnished cloth for photovoltaic module lamination technology includes and a plurality of cloth bodies still includes the elasticity strip, adjacent two be provided with one between the cloth body the elasticity strip, the elasticity strip is along a plurality of perpendicularly the array orientation of the cloth body sets up, adjacent two the tip of the cloth body all with the elasticity strip is connected. Between personally experiencing sth. Part of the body,this varnished cloth sets up the elasticity strip through the cloth adjacent for form telescopic machanism on the varnished cloth, when the offset plate compressed tightly the varnished cloth, deformation took place for elasticity strip atress, makeed the interval between the adjacent cloth body increase, and the power to toughened glass is offset in varnished cloth drawing, avoids the toughened glass dislocation, thereby